Pengaruh Kompetensi, Motivasi dan Lingkungan Kerja Guru SD Terhadap Peningkatan Mutu Berbasis Sekolah Pada Gugus I Kecamatan Witaponda Morowali - Minna Pali, Damaris; Indawati, Ninik; Ifana Sari, Yuli (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
Teachers are the spearhead in achieving national education goals. Teacher competence is needed in improving school-based quality. Schools can be qualified if the teachers are qualified. However, not all teachers are qualified, it still takes hard work to improve the quality of teachers. In addition to teacher competence, teacher motivation also influences school-based quality improvement. The research objectives are to analyze the simultaneous influence of competence, motivation, and work environment on the implementation of school-based quality improvement, the effect of competence on the implementation of school-based quality improvement, the influence of motivation on the implementation of School-Based Quality Improvement, and the influence of the work environment on the implementation of school-based quality improvement. school. The research method for the variables of competence, motivation, and work environment uses a questionnaire. As for the learning achievement variable, it uses the documentation of the value of the report card. The questionnaire was tested on 39 teachers using validity and reliability testing techniques. Hypothesis test using t-test for partial effect, and F-test for simultaneous effect. Data analysis used multiple linear regression formula with classical assumption test preceded. The results showed that: learning achievement was influenced by the variables of competence, motivation, and the work environment of elementary school teachers together significantly, competence could make a significant contribution to learning achievement, motivation could make a significant contribution to achievement, and the teacher's work environment SD can make a significant contribution to PMBS.